2016
DOI: 10.1200/jco.2015.64.0268
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase III Trial of Standard Therapy Plus Low Molecular Weight Heparin in Patients With Lung Cancer: FRAGMATIC Trial

Abstract: Purpose Venous thromboembolism (VTE) is common in cancer patients. Evidence has suggested that low molecular weight heparin (LMWH) might improve survival in patients with cancer by preventing both VTE and the progression of metastases. No trial in a single cancer type has been powered to demonstrate a clinically significant survival difference. The aim of this trial was to investigate this question in patients with lung cancer. Patients and Methods We conducted a multicenter, open-label, randomized trial to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
112
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(125 citation statements)
references
References 38 publications
9
112
1
3
Order By: Relevance
“…The updated search identifi ed eight meta-analyses (1669-9861 patients) [103][104][105][106][107][108][109][110] and six randomised clinical trials [111][112][113][114][115][116] comparing anticoagulant prophylaxis with no intervention or placebo in ambulatory patients receiving systemic anticancer therapy. Overall, a signifi cant 45·0% reduction in VTE occurrence was reported across the six meta-analyses assessing the safety and effi cacy of LMWH compared with no intervention or placebo.…”
Section: Ambulatory Patients Treated With Systemic Anticancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…The updated search identifi ed eight meta-analyses (1669-9861 patients) [103][104][105][106][107][108][109][110] and six randomised clinical trials [111][112][113][114][115][116] comparing anticoagulant prophylaxis with no intervention or placebo in ambulatory patients receiving systemic anticancer therapy. Overall, a signifi cant 45·0% reduction in VTE occurrence was reported across the six meta-analyses assessing the safety and effi cacy of LMWH compared with no intervention or placebo.…”
Section: Ambulatory Patients Treated With Systemic Anticancer Therapymentioning
confidence: 99%
“…Mortality was not diff erent between groups. The FRAGMATIC 111 multicentre, open-label, randomised trial assessed LMWH prophylaxis on 1-year survival in newly diagnosed patients with small-cell lung cancer or those with NSCLC of any stage. LMWH did not increase overall survival or metastasis-free survival.…”
Section: Khorana Predictive Model For Chemotherapy-associated Vte 10mentioning
confidence: 99%
“…Furthermore, in patients with locally advanced or metastatic pancreatic cancer receiving gemcitabine-based chemotherapy, the effi cacy and safety of primary thromboprophylaxis with LMWH, albeit at (half-) therapeutic dosages, have been demonstrated in two randomized controlled trials [93,94]. In addition, patients with lung cancer, particularly those with small-cell lung cancer and limited disease, may benefi t from primary thromboprophylaxis with LMWH [95,96].…”
Section: Rivaroxaban Apixaban Edoxaban Dabigatranmentioning
confidence: 99%
“…Lung Cancer) trial reported by Macbeth et al 1 concluded that the addition of prophylactic doses of the low molecular weight heparin (LMWH) dalteparin for 24 weeks to standard of care in patients with lung cancer did not improve overall survival; the rate of venous thromboembolism was significantly reduced but at the cost of an increase in bleeding complications. There was also no significant effect on metastasis in the group that received dalteparin.…”
Section: Matic (Dalteparin In Preventing Blood Clots In Patients Withmentioning
confidence: 99%
“…4,6 Although the authors should be congratulated for having chosen overall survival (and not only the occurrence of venous thromboembolism) as an end point, the FRAGMATIC trial was not designed to examine the antimetastatic properties of LMWHs. 1 Studies that test LMWHs with better antimetastatic properties such as tinzaparin should be conducted in a setting clearly defined for preventing metastasis. The best environment for testing an antimetastatic agent would be localized cancers that are being definitively treated by surgery or radiation together with chemotherapy.…”
Section: Matic (Dalteparin In Preventing Blood Clots In Patients Withmentioning
confidence: 99%